SPATIAL DISTRIBUTION OF MICROPLASTIC CONTAMINATION IN BLOOD CLAMS (ANADARA GRANOSA) ON THE JENEPONTO COAST, SOUTH SULAWESI (Journal of Namibian Studies : History Politics Culture, 2023)
Plastic waste in oceans will threaten of marine biota. There is a very high degree of plastic pollution in Indonesia, however the distribution of microplastic contamination in seafood, particularly that ingested by the general populace as a daily meal from seas, is quite low. The purpose of this investigation is to map the distribution of microplastic contamination in blood clams (Anadara granosa) throughout the South Sulawesi coast.Observational study employing a spatial analysis exploratory design. Blood clams (Anadara granosa) and information on wind, currents, and tides are used to map the distribution of microplastic pollution. The Kriging model was used for their geographical analysis. Purposive sampling was used to collect a total of 25 samples of blood clams (Anadara granosa) from offshore locations, residential waterways, mangrove ecosystems, rivers, and river estuaries.The results showed that the highest distribution of microplastic contamination was found in mangrove ecosystem areas and residential waters, while the lowest was found in river areas. Blood clams (Anadara granosa) have high levels of microplastic contamination because of sources of plastic pollution that come from waste disposal activities. It became stuck in the fisheries and mangrove ecosystems along the coast. Oceanography has an impact on how currents and winds migrate from the northeast (where mangrove habitats are) to the north (where residential waters are), carrying microplastic particles. Provision of waste management facilities by the local government and using the depuration method to eliminate microplastics in blood clams (Anadara granosa) consumed by the community needs to be done to reduce the impact on ecology and health.